EFEKTIVITAS PENGGUNAAN MULTIMEDIA TERHADAP PENINGKATAN MOTIVASI BELAJAR SISWA KELAS X SMA NEGERI 7 PADANGSIIDMPUAN - Mustika Ezrin Purba (PRODI PENDIDIKAN BIOLOGI, 2019)
This study aims to describe the effectiveness of use multimedia on improvement of students’ learning motivation at the tenth grade students of SMA Negeri 7 Padangsiidmpuan. The research was conducted for 3 months (April– June 2018) by applying descriptive method with 27 students as the sample and they were taken by using random sampling technique from 105 students. Observation and questionnaire were used in collecting the data. Based on descriptive analyzes, it could be found that a) the average of using multimedia was 77.14 (good category) and (b) the percentage of students’ learning motivation was 65% (effective category). It means, use multimedia on improvement of students’ learning motivation at the tenth grade students of SMA Negeri 7 Padangsiidmpuan is effective.